ZAKAT AN ECONOMIC RECOVERY INSTRUMENT POST COVID-19 PANDEMIC IN WEST NUSA TENGGARA PROVINCE - MUHAMMAD IRWAN; NUR AWWALUNNISA (Universitas Mahasaraswati K. Mataram, 2022)
The covid-19 pandemic disaster since 2020 has caused various disturbances in all aspects. In the economic aspect, there is a paralysis of economic activities caused by this pandemic so that people's incomes are affected. Besides that, people must adapt to new normal conditions during this pandemic to restore this condition. Some instruments can help in economic recovery in Islamic economics, namely zakat. The optimal management and distribution of zakat should be able to assist a country in recovering its economic condition. This study aims to analyze the role of zakat in economic recovery during the covid-19 pandemic in reducing poverty in West Nusa Tenggara Province. The method used in this research is a literature study method, both technical and non-technical literature. Based on the analysis, BAZNAS NTB has distributed zakat funds to three sectors, namely the emergency sector, health, and social sector. BAZNAS fund in 2020 record at Rp. 28.456.886.781,- and distributed as much as Rp. 27.732.619.000,- through several programs, namely BAZNAS NTB Peduli, BAZNAS NTB Takwa, BAZNAS NTB Sehat, BAZNAS NTB Makmur, BAZNAS NTB Cerdas, etc. in 2020 BAZNAS NTB has prepared Rp. 700.000.000,- ti assist the NTB government in dealing wih the covid-19 pandemid. In 2021 BAZNAS NTB has received zakat funs of Rp. 31.500.000.000, which is ready to be distributed through programs in BAZNAS NTB